How do you simplify \[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}}\]?
Answer
Verified
444k+ views
Hint:When one term is raised to the power of another term, the function is called an exponential function, for example \[a = {x^y}\] . The inverse of the exponential functions are called logarithm functions, the inverse of the function given in the example is\[y = {\log _x}a\] that is a logarithm function. These functions also obey certain rules called laws of the logarithm, using these laws we can write the function in a variety of ways. Using the laws of the logarithm, we can solve the given problem.
Complete step by step solution:
Given,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}}\].
We know the logarithm quotient rule that the logarithm of the ratio of two quantities is the
logarithm of the numerator minus the logarithm of the denominator.
That is \[\ln \left( {\dfrac{m}{n}} \right) = \ln m - \ln n\]. Applying this in the numerator term we have,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}} = \dfrac{{\ln (1) - \ln (4)}}{{\ln 2}}\]
We know that \[\ln (1) = 0\].
\[ = \dfrac{{0 - \ln (4)}}{{\ln (2)}}\]
\[ = - \dfrac{{\ln (4)}}{{\ln (2)}}\]
But we can write \[4 = {2^2}\]then
\[ = - \dfrac{{\ln ({2^2})}}{{\ln 2}}\]
We know the logarithm power rule that the logarithm of an exponential number is the exponent times the logarithm of the base.
That is \[\ln ({m^n}) = n\ln (m)\]. Applying this we have
\[ = - \dfrac{{2\ln (2)}}{{\ln (2)}}\]
\[ = - 2\]
Thus we have
\[ \Rightarrow \dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}} = - 2\]
Note: the above problem can be solved easily by only using the power rule,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}}\],
Since we can write \[\dfrac{1}{4}\] as \[\dfrac{1}{{{2^2}}}\]
\[ = \dfrac{{\ln \left( {\dfrac{1}{{{2^2}}}} \right)}}{{\ln 2}}\]
Rearranging we have
\[ = \dfrac{{\ln \left( {{2^{ - 2}}} \right)}}{{\ln 2}}\]
We know the logarithm power rule that is \[\ln ({m^n}) = n\ln (m)\]. Applying this we have
\[ = \dfrac{{ - 2\ln \left( 2 \right)}}{{\ln 2}}\]
\[ = - 2\]. In both cases we have the same answer.
The important condition while applying the laws of the logarithm is that the base of the logarithm functions involved should be the same in all the calculations. Here we have a natural logarithm function that is base\['e'\]. If they simply given \[\log x\] then we take the standard base that is 10.
Complete step by step solution:
Given,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}}\].
We know the logarithm quotient rule that the logarithm of the ratio of two quantities is the
logarithm of the numerator minus the logarithm of the denominator.
That is \[\ln \left( {\dfrac{m}{n}} \right) = \ln m - \ln n\]. Applying this in the numerator term we have,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}} = \dfrac{{\ln (1) - \ln (4)}}{{\ln 2}}\]
We know that \[\ln (1) = 0\].
\[ = \dfrac{{0 - \ln (4)}}{{\ln (2)}}\]
\[ = - \dfrac{{\ln (4)}}{{\ln (2)}}\]
But we can write \[4 = {2^2}\]then
\[ = - \dfrac{{\ln ({2^2})}}{{\ln 2}}\]
We know the logarithm power rule that the logarithm of an exponential number is the exponent times the logarithm of the base.
That is \[\ln ({m^n}) = n\ln (m)\]. Applying this we have
\[ = - \dfrac{{2\ln (2)}}{{\ln (2)}}\]
\[ = - 2\]
Thus we have
\[ \Rightarrow \dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}} = - 2\]
Note: the above problem can be solved easily by only using the power rule,
\[\dfrac{{\ln \left( {\dfrac{1}{4}} \right)}}{{\ln 2}}\],
Since we can write \[\dfrac{1}{4}\] as \[\dfrac{1}{{{2^2}}}\]
\[ = \dfrac{{\ln \left( {\dfrac{1}{{{2^2}}}} \right)}}{{\ln 2}}\]
Rearranging we have
\[ = \dfrac{{\ln \left( {{2^{ - 2}}} \right)}}{{\ln 2}}\]
We know the logarithm power rule that is \[\ln ({m^n}) = n\ln (m)\]. Applying this we have
\[ = \dfrac{{ - 2\ln \left( 2 \right)}}{{\ln 2}}\]
\[ = - 2\]. In both cases we have the same answer.
The important condition while applying the laws of the logarithm is that the base of the logarithm functions involved should be the same in all the calculations. Here we have a natural logarithm function that is base\['e'\]. If they simply given \[\log x\] then we take the standard base that is 10.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE